Using of collars “Neoterika Protecto 12” against ixodid ticks in dogs and cats - M. V. Arisov; G. B. Arisova; E. A. Koshkarev; I. A. Stepanova (Российский паразитологический журнал, 2019)
The purpose of the research: to study the effectiveness of the insectoacaricidal collars “Neoterika Protecto 12” against Ixodid ticks in dogs and cats. Materials and methods. In the experiment 86 dogs and 24 cats of different ages and breeds, free from ectoparasites, were used. 30 days before the experiment, the animals were not treated with antiparasitic drugs and they did not use insectoacaricidal collars for three months. All animals were divided into experimental and control groups. The animals of the experimental groups “Neoterika Protecto 12” were used according to the instructions for use. Animals of the control groups did not receive the collar. Inspection of animals for mites was carried out regularly for 6 months. Studies were conducted on the territory of the Moscow, Ryazan and Nizhny Novgorod regions. Results and discussion. For 6 months ectoparasites on the skin-coat of animals is not fixed. Side effects after use of the collar were not observed. When studying animals of control groups for 6 months found attached Ixodid ticks, as well as fleas Ctenocephalides felis and C. canis. After ectoparasites were found in control animals, the collars were also put on the animals, previously removing the ticks, and continued to observe for 6 months. No ectoparasites were found on the skin-coat. The high prophylactic and therapeutic efficacy of collars “Neoterika Protecto 12” was established against ectoparasites, including ticks, during 6 months.